ANALISIS PENGGUNAAN BAHASA INDONESIA DAN KEARIFAN LOKAL YANG TERDAPAT PADA FILM IMAM TANPA MAKMUM - Dalimunthe, Elvi Susana; Amaliyah, Raudhatul; Mangunsong, Sri Emelda; Manik, Alan Kibar; Harahap, Safinatul Hasanah (Ma Chung Press, 2024)
Film